Analysis of Electromagnetic Simulation Method for the Dielectric Lens Antenna - Ansarudin, Farizah; Abd. Rahman, Tharek; Yamada, Yoshihide; Abd Rahman, Nurul Huda (International Journal of Integrated Engineering, 2020)
For the millimetre wave usage at 5G mobile communication system, a dielectric lens antenna will become a promising candidate for the base station antenna. In developing a dielectric lens antenna, antenna performance analysis by an electromagnetic simulator will be necessary. The structure of the proposed design is a hyperbolic dielectric lens antenna fed by a pyramidal horn at the operating frequency of 28GHz. In this paper, the abilities of a commercial electromagnetic simulator FEKO are investigated. Simulation methods of GO and MoM solvers are shown for electric field distributions on the antenna aperture and far field radiation patterns. The simulation results show that the optimum gain of lens antenna based on GO and MoM method are 26.68 dBi and 27.24 dBi, respectively. Moreover, multi beam radiation patterns and suitable feed positions are clarified for wide scanning angle. Good performance for multi beam application by using MoM is shown based on the off-focus characteristic where the antenna gain is only slightly reduced from 0.51 dBi to 4.03 dBi for 5.71Â° to 35.54Â°.